An empirical assessment of a modified artificially intelligent device use acceptance model—From the task-oriented perspective - Yang, Yutao; Luo, Jia; Lan, Tian (Frontiers in Psychology, 2022)
Artificial intelligence (AI) is a cutting-edge technology that has been widely applied in tourism operations. To enhance tourists’ experience, many tourism suppliers introduced AI devices to interact with tourists. Previous studies classified AI devices as task- and social- oriented based on their functions; however, current models that explain customers’ intention to use AI devices did not reflect the discrepancy between the two different types. Therefore, this paper attempts to fill this gap by proposing a theoretical model for the use of task-oriented AI devices. Based on the multi-stage appraisal framework and the Structural Equation Modeling analysis, this paper presents the following findings: (1) utilitarian motivation, interaction convenience, and task-technology fit are the factors appraised in the first stage; (2) perceived competence and flow experience are the factors appraised in the second stage; (3) utilitarian motivation, interaction convenience, and task-technology fit are positively associated with perceived competence. (4) perceived competence positively influences flow experience, which further affects customers’ switching intention from task-oriented AI devices to human service; (5) The serial mediating effect of perceived competence and flow experience between the stimulus mentioned in the first appraisal stage and the switching intention is confirmed. This study reveals the underlying psychological mechanism when customers use task-oriented AI devices, and it provides a theoretical framework for task-oriented AI device adoption.